Mindfulness Interventions for Emotion Regulation and Anxiety in Deaf and Hard-of-Hearing Students - Putri Indah Septiani; Elsa Efrina; Marlina Marlina; Antoni Tsaputra; Putri Indah Septiani; Elsa Efrina; Marlina Marlina (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
The purpose of this study is to investigate the features, efficacy, and adaptations of mindfulness-based interventions to enhance regulation of emotion and reduce anxiety in students with Deaf and Hard-of-Hearing conditions. We performed a systematic literature review with bibliometric analysis which was based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Through the Scopus database and relevant articles, 563 results were generated. Quality synthesis of data 10 studies were selected following removal of duplicates and application of inclusion criteria. Results suggest that mindfulness-based interventions contribute to improved emotion regulation, specifically increases in emotional awareness, self-control and adaptive coping strategies among Deaf and Hard-of-Hearing students. These interventions may also indirectly reduce anxiety by strengthening internal psychological qualities. Nevertheless, most of the interventions are not carried out using just mindfulness but through wider approaches such as psycho-education and emotional intelligence. Additionally, the accessibility adaptations, such as visual supports and sign language (SL) use, seem to have a great impact on the efficacy of mindfulness interventions across different disabilities or conditions. While these results are promising, the literature reflects an absence of experimental studies and treatment protocols tailored to this population. Future research should seek to create effective, low resource counselling protocols suited to the specific needs of students with Deaf and Hard-of-Hearing conditions.